2003
DOI: 10.1176/appi.ajp.160.11.1946
|View full text |Cite
|
Sign up to set email alerts
|

Functional Neuroanatomy of Grief: An fMRI Study

Abstract: Grief is mediated by a distributed neural network that subserves affect processing, mentalizing, episodic memory retrieval, processing of familiar faces, visual imagery, autonomic regulation, and modulation/coordination of these functions. This neural network may account for the unique, subjective quality of grief and provide new leads in understanding the health consequences of grief and the neurobiology of attachment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
167
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 249 publications
(187 citation statements)
references
References 30 publications
17
167
1
1
Order By: Relevance
“…If one group showed significant activation in a region (p< .005, 10 voxels), we reported the activation from that same coordinate in the other group (Table 1). Each group showed significant activity in pain-related regions (dACC, insula, PAG) in the comparisons of the deceased vs. stranger pictures and grief vs. neutral words (Table 1), as has been previously shown in NCG (Gündel et al, 2003). The only activity in pain-related regions that differed between groups was in the left insula (x=−34, y=14, z=18), which was more active in the NCG group during the viewing of grief-related vs. neutral words (t=4.20, p<0.001, 87 voxels).…”
Section: Pain Network Activationsupporting
confidence: 74%
See 1 more Smart Citation
“…If one group showed significant activation in a region (p< .005, 10 voxels), we reported the activation from that same coordinate in the other group (Table 1). Each group showed significant activity in pain-related regions (dACC, insula, PAG) in the comparisons of the deceased vs. stranger pictures and grief vs. neutral words (Table 1), as has been previously shown in NCG (Gündel et al, 2003). The only activity in pain-related regions that differed between groups was in the left insula (x=−34, y=14, z=18), which was more active in the NCG group during the viewing of grief-related vs. neutral words (t=4.20, p<0.001, 87 voxels).…”
Section: Pain Network Activationsupporting
confidence: 74%
“…These photos and words were made into 60 composites (Figure 1), each consisting of one picture (deceased or stranger) and one word (grief-related or neutral). Empirical support for the grief-eliciting task has been shown previously using both skin conductance methodology and participants' subjective reports (Gündel, O'Connor, Littrell, Fort, & Lane, 2003). Participants viewed composites through goggles in randomized order.…”
Section: Methodsmentioning
confidence: 92%
“…The rating was completed following scanning so that it did not contaminate emotional experience or its neural substrates. As reported in Gündel et al (2003), the four conditions differed in subjective ratings of grief and skin conductance responses (po0.05), suggesting that the different conditions reliably elicited distinct levels of grief.…”
Section: Task Design and Stimulisupporting
confidence: 51%
“…We have previously used personalized stimuli in eliciting grief in the imaging environment (Gündel et al, 2003). To expand the understanding of the CNS-ANS relationship, the present study investigated the association between the regional brain activity during the evocation of grief in these participants and unpublished data on their baseline parasympathetic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have also reported altered activity in the cerebellum and posterior inferior temporal cortex bilaterally with grief or sad mood provocation in healthy and depressed subjects (Gundel et al, 2003;Liotti et al, 2002), suggesting that these regions form part of the ventral neural system mentioned above. The increases seen in occipital and superior cerebellar rCBF independent of mood change may suggest that the posterior (visuospatial) attentional system may also be affected by RTD.…”
Section: Discussionmentioning
confidence: 78%